PROBLEMS AND CHALLENGES OF HIGHER EDUCATION SCENARIO OF ASSAM - Mr. Uttam Mili (Elementary Education Online, 2023)
Achievement of human development in a sustained and equitable perspective is a subject of great challenge in the present Indian society. Although notable progress has been observed over all the aspects, deprivation of a large section of the society from education, health care facilities and other economic resources due backwardness and poverty is hindering the human resource development of the state. Higher education is a most crucial mandate to bridge the gap between knowledge and man. It is one of the most crucial indices for socio-economic development. A good sound beginning in the field of higher education is important for overall flourishing of the socio-political sphere. However, Higher Education sector in India in general and in Assam in particular, has not been able to contribute its outmost role in the sphere of Human Resource Development. Higher education scenario in Assam has changed in past 10 years. A proper commitment to this sector can bring a much-needed change which in turn may revolutionize the overall growth and development. In this paper, an attempt has been made to highlight the changes observed in the higher education scenario prevailing in Assam. The study also identifies the problems and prospects of with a special reference to the higher education sector of Assam.